Особливості виробництва молока корів голштинської породи - Євлахович, Альона Олександрівна; Evlakhovich, А. О.; Карлова, Ліна Валентинівна; Karlova, L. V.; Karlova, L.; Karlova, Lina V.; Karlova, Lina Valentinovna; Karlova, Lina Valentunivna; Karlova, Lina; Деберина, Ірина Володимирівна; Deberina, Irina; Deberina, I. V. (Дніпровський ДАЕУ, 2020)
Наведено результати досліджень експлуатації первісток залежно від тривалості їх ембріогенезу за сучасних умовах виробництва молока. Встановлено, що за рівнем продуктивних ознак переважали особини з коротким ембріогенезом. За компонентним складом молоко в усіх дослідних тварин було якісне і відповідало встановленим вимогам. Було визначено вплив лінійної належності первісток на тривалість їх ембріонального розвитку та економічну доцільність їх використання. The results of research on the exploitation of firstborns depending on the duration of their embryogenesis under modern conditions of milk production are presented. It was found that the level of productive traits was dominated by individuals with short embryogenesis. In terms of component composition, the milk of all experimental animals was of good quality and met the established requirements. The influence of linear affiliation of first-borns on the duration of their embryonic development and economic feasibility of their use was determined.
Features of production of milk of cows of голштинської of breed
Карлова Ліна Валентинівна https://orcid.org/0000-0001-8213-8588
Keywords: економічна ефективність; economic efficiency; корови; cows; ембріогенез; embryogenesis; якість молока; milk quality; продуктивність; productivity